2009
DOI: 10.1016/j.jpsychires.2008.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Enduring effects of severe developmental adversity, including nutritional deprivation, on cortisol metabolism in aging Holocaust survivors

Abstract: Objective In animal models, early life exposure to major environmental challenges such as malnutrition and stress results in persisting cardiometabolic, neuroendocrine and affective effects. While such effects have been associated with pathogenesis, the widespread occurrence of ‘developmental programming’ suggests it has adaptive function. Glucocorticoids may mediate ‘programming’ and their metabolism is known to be affected by early life events in rodents. To examine these relationships in humans, cortisol me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 50 publications
5
57
2
1
Order By: Relevance
“…Elderly survivors of the World War II Holocaust display threefold lower 5a-reduction of cortisol, indicative of reduced hepatic 5a-reductase type 1 activity (Yehuda et al 2009a). The greatest reductions in 5a-reductase activity were observed in those individuals who were the youngest at exposure to the Holocaust, indicating a potential 'programming' window in early life.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Elderly survivors of the World War II Holocaust display threefold lower 5a-reduction of cortisol, indicative of reduced hepatic 5a-reductase type 1 activity (Yehuda et al 2009a). The greatest reductions in 5a-reductase activity were observed in those individuals who were the youngest at exposure to the Holocaust, indicating a potential 'programming' window in early life.…”
Section: Discussionmentioning
confidence: 97%
“…Programming of altered peripheral glucocorticoid metabolism has been reported in models of prenatal glucocorticoid overexposure with documented changes in hepatic and renal 11bHSD1 expression (Nyirenda et al 2009, Tang et al 2011. Additionally, reduced 5a-reductase activity has been proposed as an important contributor to the 'programmed' phenotype seen in individuals exposed to the severe physical, nutritional and psychological challenges of the World War II Holocaust early in life who subsequently developed post-traumatic stress disorder (PTSD; Yehuda et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…The HSD11B2 gene promoter is subject to methylation (17). Children exposed to the horrors of the Nazi Holocaust have reduced renal 11␤-HSD2 activity in old age with the greatest effect seen in those youngest at traumatization (797). These data suggest 11␤-HSD2 is a programming target in humans, possibly to maximize renal sodium retention in what may be anticipated to be a starvation-associated sodium-poor environment.…”
Section: Deficient Placental 11β-hsd2mentioning
confidence: 92%
“…Exceptions were cortisol and some of its metabolites. Yehuda et al 29 found significantly lower 5a-reductase activity in Holocaust survivors and suggested that its reduction may be associated with a vulnerability to development of PTSD. The highest amygdala activation in non-responders and highest anterior cingulate cortex volume in responders before treatment are compatible with the current model of PTSD 30,31 , which is based in neuroimaging data that show exaggerated amygdala activation and decreased activation in frontal areas.…”
Section: Biological Correlates Of Response Predictionmentioning
confidence: 99%